Correlation between Cytology and Histology of Solitary Thyroid Nodule: Our Institutional Experience - Thakur, R.; Thakur, S.K. (Journal of Diabetes and Endocrinology Association of Nepal, 2021)
Introduction: Thyroid swelling is one of the most common disease presenting to otorhinolaryngology out patient. Fine needle aspiration cytology is key point in planning the surgical management. The discrepancy between cytology and histology reported in wide range depending upon centres. We planned to conduct this study with aim of knowing the sensitivity of cytology which can guide the need of surgical or observational treatment. Methods: Our study is prospective enrolling the patients with thyroid swelling who underwent surgical treatment between 1st October 2020 to 11th November 2021. Clinical, cytological and histological parameters were recorded. Accounting histology as gold standard, sensitivity, specificity and accuracy of fine needle cytology were calculated. The correlation was evaluated by chi square test. The p value of ≤0.05 was considered significant. Results: The most common age group reporting was 20-40 years accounting for 68.6% of cases with the female predominance (92.2%). The accuracy of fine needle cytology in detecting non neoplastic, neoplastic benign and neoplastic malignant lesion were 96.0%, 96.0% and 100.0 % respectively. Conclusions: Fine needle cytology is good tool for deciding surgical management for thyroid nodule and recommended for all cases.